Hubungan Status gizi, Anemia, Faktor Stress dan Kualitas Tidur dengan Siklus Menstruasi Remaja di Pesantren - Kartika Pibriyanti; Mardhatillah Mardhatillah; Lulu’ Luthfiya; Amilia Yuni Damayanti; Indahtul Mufida; Cut Kemala Handayani; Reni Indrayanti Fernandes (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Infertility is a global health problem that affects millions of reproductive age worldwide. Infertility can be caused by menstrual cycle problems. Menstrual cycles altered often occur in adolescents with a prevalence of >65%. Changes in the menstrual cycle are influenced by several factors to avoid complications adolescents expected to monitor their menstrual cycle. This research was an observational quantitative research with cross-sectional method. The result of this research were most respondents aged 12 years as many as 62 respondents (64.6%). Most respondents had normal nutritional status of 76 respondents (79.2%) with the number of non-anemic respondents as many as 73 respondents (76%). Most of the respondents experienced stress as many as 83 respondents (86.5%) and poor sleep quality as many as 70 respondents (72.9%). Meanwhile, the most common menstrual cycle disorder was Amenorrhea with 70 respondents (72.9%). In this research it can be concluded that there was no relationship between nutritional status (p=1.000), stress factors (p=0.744), sleep quality (p=1.000) and menstrual cycle in adolescents at Boarding School but there was a relationshop between anemia and menstrual cycle in adolescents at Boarding School (p=0.022).